Realitas Dinamika Integrasi Sosial Etnis Jawa dan Lampung di daerah Pardasuka Kabupaten Pringsewu - Retno Putri; M. Fadhil Nurdin; Muhammad Fedriansyah; Junaidi Junaidi (Universitas Negeri Medan, 2019)
When the community only sees integration as limited as the meaning of tolerance, the dynamics of social integration through different ethnic social exchanges in the Pringsewu District Pardasuka area are interesting to study. The aim is to provide an understanding and knowledge of social integration in the wider community. This study certainly uses qualitative methods with case study analysis. Data collection techniques use observation, documentation, and interview techniques. The informant withdrawal is done by using purposeful sampling which is continued with the Snowball sampling technique. The research informants were drawn from the Javanese and Lampung ethnic communities which formed integration through social exchange. Documentation data is taken from the archives of the Pardasuka area. Then, from the results of interviews, observation and documentation is done reduction, analysis, and triangulation of all data that are considered necessary, so as to provide valid conclusions. From the results of the study show that, the social integration between Javanese ethnic and ethnic Lampung that occurred in the Pringsewu district Pardasuka area can integrate well. Social exchange is done as a bridge of interaction to obtain long-term agreements, so that the community can preserve its integration.